FAKTOR YANG MEMPENGARUHI RENDAHNYA MINAT BACA MASYARAKAT DI TAMAN BACAAN KOTA PEKANBARU - Tri Handoko; Wilson '; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study are (1) for a description of the visit in the public reading of Pekanbaru, (2) internal factors affecting low reading public interest in the public reading of Pekanbaru, (3) external factors affecting low public interest in reading in the park Pekanbaru city public reading. The type of research conducted is a qualitative description with a descriptive case study approach aims to determine the factors that affect the low reading public interest in the park reading the city of Pekanbaru. Where the research was conducted in TBM Pekanbaru located on the road Tambelan state parks white wood village Simpang Empat Pekanbaru. TBM Pekanbaru are investigating a given range of issues concerning the public interest, Pekanbaru. Subjects in this study were 3 people consisting of one person kasudit services library and archives Pekanbaru, one employee TBM Pekanbaru and one of the visitors who will be used as informants. Data collection techniques are the ways that researchers to collect data, the study was conducted through the following steps: observation, interviews, documentation, triangulation. To determine the factors that affect low reading public reading public in the city of Pekanbaru. The researchers collecting data in accordance with the guidelines of data collection techniques are available, the obtained results of the research findings tendency to lower the public interest in TBM city of Pekanbaru influenced by internal factors which include aspects of age and psychological needs of visitors, while external factors covering aspects of availability book, infrastructure, and teman.Didasarkan influence on the outcome of the above data it can be concluded that the research results the dominant factor affecting low reading public interest in Pekanbaru city TBM are external factors which include covering aspects of availability of books, facilities, and the effect teman.Untuk recommendation that researchers aimed for managers as the executor TBM management of Pekanbaru city, the library board and archives Pekanbaru city as the policy makers in the development of culture in the city of Pekanbaru, as well as the parties that support the cultivation of reading interest, especially in the city of Pekanbaru.Keywords: interest in reading, community, public reading